1995
DOI: 10.1016/0304-3835(95)92759-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell growth inhibition by several Annonaceous acetogenins in an in vitro disk diffusion assay

Abstract: The cell inhibition activities of several Annonaceous acetogenins, covering the three major structural classes of bis-adjacent, bis-non-adjacent, and single tetrahydrofuran (THF) ring compounds and their respective ketolactone rearrangement products, were tested in an in vitro disk diffusion assay against three murine (P388, PO3, and M17/Adr) and two human (H8 and H125) cancerous cell lines as well as a non-cancerous immortalized rat GI epithelial cell line (I18). The results demonstrate a dose-dependent inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 17 publications
1
67
0
3
Order By: Relevance
“…Cancer cells had an unusual action mechanism of energy conservation such as higher respiration and energy production, and this kind of energy metabolism made it more easily inhibited by ACG than normal cells. 15) However, ACG were fairly toxic to normal cells in vivo or vitro, their toxicity was hundreds or thousands of times higher than KCN, which is a virulent chemical reagent. 16) This resulted in the restricted use of ACG as anticancer drugs in the clinical area.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer cells had an unusual action mechanism of energy conservation such as higher respiration and energy production, and this kind of energy metabolism made it more easily inhibited by ACG than normal cells. 15) However, ACG were fairly toxic to normal cells in vivo or vitro, their toxicity was hundreds or thousands of times higher than KCN, which is a virulent chemical reagent. 16) This resulted in the restricted use of ACG as anticancer drugs in the clinical area.…”
Section: Resultsmentioning
confidence: 99%
“…符合本综述要求的化合物为 55 个(见表 1). 除了本 文总结的构效关系之外, 据文献报道 [7,10,12,38] , 单四氢呋 喃型番荔枝内酯尤其是无 4-OH 时活性最低, 而邻双四 氢呋喃型番荔枝内酯活性最高, 其次是间双四氢呋喃型 番荔枝内酯. α,α'-二羟基取代邻双四氢呋喃型番荔枝内 酯类化合物的活性要强于 α-单羟基取代邻双四氢呋喃 型番荔枝内酯类化合物 [22] .…”
Section: 邻位双四氢呋喃型 Thf 两 侧 各 有 一 个 羟 基 相 邻 的 相 对 构 型 有 Th/t/th/t/th Eunclassified
“…Both mechanisms of action result in the inhibition of ATP production and may account for the observation that AGEs are more effective at killing multiple-drug resistant (MDR) tumours than their nonresistant counterparts since the MDR pumps on the cell membranes require ATP to function. In addition, Oberlies et al observed that AGEs could selectively inhibit the cell growth of cancerous cells by in vitro cell inhibition assays against three murine (P388, PO3, and M17/Adr) and two human (H8 and H125) cancer cell lines [69]. Interestingly, the work of Oberlies et al proposed that this class of natural products showed a certain biological activity against some drug-resistant cancers.…”
Section: Biological Activities and The Mechanisms Of Action Of The Agesmentioning
confidence: 99%